Analisis Pelaksanaan Perizinan Laboratorium di Wilayah Kerja Dinas Kesehatan Provinsi Sumatera Selatan - Kushandayani, Ratih; Lisdiana, Lisdiana; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2026)
The problems in this study included business actors/applicants not being understand about laboratory licensing requirements in the OSS application and business actors/applicants not understanding how to input the application in OSS. This study used interview instruments with research informants, observation and literature study. The data used consists of qualitative data and quantitative data sourced from primary data and secondary data. The data were analyzed through stages: sorting, analysis/discussion, and drawing conclusions. From the results of the research, it is known that the implementation of Laboratory Licensing in the Work Area of the Provincial Health Office has been carried out well, but there are still obstacles in the aspect of mobilizing/implementing it. The implementation of Community Training and Protection from the planning aspect has been carried out in accordance with the applicable guidelines and regulations. In the organizational aspect, there is an implementation team in implementing Laboratory Licensing in the Work Area of the Provincial Health Office. The main tasks and functions are carried out properly by the implementing team. In the mobilization aspect, it is known that there are still weaknesses where business actors or the public seem to still not understand the procedure for inputting into the OSS application. So that at the time of submission it is necessary to input it first. Supervision seen from the aspect of monitoring and reporting is known to have been carried out properly according to the implementation guideline